Formation of professional competence of the future teachers of physical training by methods of pedagogical situations. - Chernyakov V.V (Kharkov National Pedagogical University, 2011)
The model of usage of pedagogical situations during professional training of the future teachers of physical training is shown. In creation of model is used practical experience of usage of pedagogical situations during teaching and educational process at faculty of physical training. Efficiency of application of pedagogical situations during formation of professional competence of the future teachers of physical training is proved. The main element of the technology of forming professional competence was research and problem-educational tasks that stimulate students' activity.